Pengaruh Status Sosial Ekonomi Orang Tua Dan Gaya Hidup Terhadap Perilaku Konsumtif Siswa-Siswi Kelas XI SMAN 1 Tulungagung Tahun Pelajaran 2021/2022 - Yuliana Wulandari; Sri Wulan Yanuari (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2022)
Students today are, in a sense, modern, fashionable societies that are up to date and fashionable. Today's purchase is not for meeting needs but for satisfying desires, it has led to social pride among youth, resulting in consumption behaviors in youth are no longer at the scale of their priorities, In this research the methods of data collection using an angket. Using the instrument test, prerequisite test, hypothetical test, data analysis techniques using a linear regression. The results of the study are the positive and significant social status of parents' students, acquired thitung (3.560) > ttable (1.993) with a degree of significance 0.001 0.05. Lifestyles have a positive and significant impact on student consumptive behavior. Under thitung (3.350) > ttable (1.993) and Significance rate 0.001 < 0.05. The social status of parents and life-style together have significant impact on consumptive behavior. Ftable (16.146) > ftable (3.12) and a significant rate of 0,000 0.05, resulting in ho3 being rejected and ha3 being accepted. This suggests that there are significant effects of the variables of the social status of parents and life-styles towards confoctive behavior. So it can be said that 31.3% of consumer behavior is influenced by the social status of parents and lifestyle, while the rest is 68.7% influenced by other variables not studied in the study